Authenticity and ideology: Creating a culture of authenticity through reflecting on purposes for learning and teaching - Pinner, Richard (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This paper discusses some of the troubling issues which surround the nature of authenticity in language teaching and learning, such as identity, the legitimacy of L2 teachers of English, and the disempowerment of L2 voices. This paper presents an examination uncovering how the English language is marketed to learners, and traces the effect this has on our teaching approach and sense of efficacy as language teachers. Rather than simply ‘real language’ or ‘newspapers’, I propose that authenticity should be taken to mean that learning is both personally meaningful and socially relevant to each individual in context. Fundamentally, this paper argues that as teachers we must find our own authentic reasons for working with students, in order to create a culture of authenticity in the language classroom.